Imagens da memória: mudanças na paisagem urbana de Tocantinópolis - Silva, Simone Rodrigues da (Universidade Federal do Tocantins, 2021)
The events of a place, a people or a city will only become history if they remain alive in the memory of those who participated in them. From these memories are images that can be translated and transformed into stories and documents. This work was built with the intention of keeping alive a little of the history of Tocantinópolis through the materialization of the memories of some scenarios and events that were modifying the landscape of this city from its urban development. The data collected here were collected through informal conversations with former residents and to understand more about the history of the city, support was sought in the writings of some authors who wrote and wrote about Tocantinópolis, such as: CORREIA (1977), SOUSA (2008), PEREIRA (2012), PEREIRA (2007), among others. Searching and writing about the history of this bicentennial city was more than an exercise, brought the uneasiness that it is necessary to give voice to the images of the memories of former residents in order to rebuild the little of the cultural patrimony that still exists, so that the new generations know and value.